Metabolic profile and body weight of piglets fed with different levels of phosphorus in distinct thermal environments - Dantas, Waleska de Melo Ferreira; Ribeiro Filho, José Dantas; Guimarães, José Domingos; Guimarães, Simone Eliza Facioni (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effect of diets with different available phosphorus contents on metabolic profile and on body weight of piglets at baseline, maintained in distinct thermal environments. One hundred and twenty barrow piglets from commercial strain and with an average body weight of 15 kg were used. The treatments consisted of diets with 0.107, 0.214, 0.321, 0.428, and 0.535% available phosphorus, and of two environments: thermoneutral and warm. Body weight was determined at the beginning and at the end of the experimental period, and blood samples were taken for measuring electrolytes, albumin, total protein, nitrogenous substances, total and bone alkaline phosphatase, thyroid hormones, glucose, and lactate. Both diets and environments had effect on body weight gain and on the values of sodium, potassium, total calcium, magnesium, phosphorus, total and bone alkaline phosphatase, free T4, and lactate. The increase in phosphorus contents in the diet has a positive effect on body weight in the studied environments, but it unbalances blood calcium:phosphorus relations. Heat stress decreases the levels of glucose, total alkaline phosphatase, and free T4 in the blood, and increases those of lactate. Blood biochemical parameters reflect the metabolic state of the animals and can be used to evaluate nutritional balance and for early detection of metabolic alterations.